Refinement of the chromosome 5p locus for familial calcium pyrophosphate dihydrate deposition disease. - Andrew, L; Brancolini, V; de la Pena, L; Devoto, M; Caeiro, F; Marchegiani, R; Reginato, A; Gaucher, A; Netter, P; Gillet, P; Loeuille, D; Prockop, D; et al. (1999)
Familial calcium pyrophosphate dihydrate deposition disease (CPPDD) is a disease of articular cartilage that is radiographically characterized by chondrocalcinosis due to the deposition of calcium-containing crystals in affected joints. We have documented the disease in an Argentinean kindred of northern Italian ancestry and in a French kindred from the Alsace region. Both families presented with a common phenotype including early age at onset and deposition of crystals of calcium pyrophosphate dihydrate in a similar pattern of affected joints. Affected family members were karyotypically normal. Linkage to the short arm of chromosome 5 was observed, consistent with a previous report of linkage of the CPPDD phenotype in a large British kindred to the 5p15 region. However, recombinants in the Argentinean kindred have enabled us to designate a region<1 cM in length between the markers D5S416 and D5S2114 as the CPPDD locus.